Contingent self-definition and amorphous regions: A dynamic approach to place brand architecture. (March 2018) - Dinnie, Keith
This article explores the concept of contingent self-definition, whereby place brands employ flexible self-definitional approaches in constructing their place brand architecture. Adopting a view of regions as social constructs, the article builds on and extends previous work on place brand architecture by identifying the underlying factors that drive contingent self-definition decisions. Based on an empirical study of professionals tasked with managing region brands in the Netherlands, 11 factors are identified as drivers of contingent self-definition by place brands. These factors are grouped into four thematic categories: (i) external perceptions, (ii) proximity, (iii) brand relationships, and (iv) politics and power. A dynamic approach to place brand architecture is advocated, foregrounding the amorphous character of regions as social constructs that defy reification solely as fixed territorial-administrative spaces.